VALUE PROPOSITION ANALYSIS TELKOMSEL LOOP CARD PRODUCTS - Gayatri Putri Mubandari; Sri Hartini (SEAN Institute, 2023)
This study aims to analyze marketing strategies and value propositions offered by Telkomsel LOOP card products. This study used a descriptive qualitative method. Data collection methods carried out in this study were interviews, observation, and documentation. This study uses an analysis of 11 value proposition elements Osterwalder and Pigneurn (2014). The results of the analysis show that the new nature of LOOP cards has a youth segment, has uneven network performance, LOOP cards adjust services offered with youth, completes work with Ruangguru learning applications, has a design that is characterized by youth, has brand or card status for young creative and inspirational, has a cheap price offer according to youth, reduced fees from promos, reduced risk of credit reminders and quotas and 24-hour call center, ability to access from the MyTelkomsel, LOOPkita application and comfort and usability when registering cards and choose internet package. Therefore, LOOP cards can position products according to their youth segment.